Computational Forensics Second International Workshop, IWCF 2008, Washington, DC, USA, August 7-8, 2008, Proceedings - Srihari, Sargur N.; Franke, Katrin (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2008)
This book constitutes the refereed proceedings of the Second International Workshop, IWCF 2008, held in Washington, DC, USA, August 2008. The 19 revised full papers presented were carefully reviewed and selected from 39 submissions. The papers are organized in topical sections on trends and challenges; scanner, printer, and prints; human identification; shoeprints; linguistics;decision making and search; speech analysis; signatures and handwriting.